Risk Factors for Mortality in Melioidosis: A Single-Centre, 10-Year Retrospective Cohort Study - Raviraj Menon; Poornima Baby; Anil Kumar V.; Sandeep Surendran; Manu Pradeep; Aiswarya Rajendran; Gaayathri Suju; Arathy Ashok (The Scientific World Journal)
Melioidosis is a tropical infectious disease with diverse clinical presentations. We aimed to investigate the characteristics and mortality risk factors of patients diagnosed with melioidosis in the past 10 years. This was a retrospective cohort study conducted at a quaternary care centre in South India. Clinical, demographic, and biochemical data in patients diagnosed with melioidosis with cultures were collected between January 2011 and December 2020 from medical records. Logistic regression analysis was performed to screen mortality risk factors of melioidosis in addition to descriptive statistics and chi-square analysis. Seventy-three melioidosis patients’ records were analysed, and the most common comorbidity was type 2 diabetes mellitus (n = 53, 72.6%). The patients showed diverse presentations: pulmonary involvement, 30 (41.1%); splenomegaly, 29 (39.7%); abscesses and cutaneous involvement, 18 (24.7%); lymph node, 10 (13.7%); arthritis and osteomyelitis, 9 (12.3%); and genitourinary infection, 4 (5.4%). The mortality was noted to be 15 (20.5%). Logistic regression analysis indicated that chronic kidney disease (OR = 14.0), CRP >100 IU/L (OR = 6.964), and S. albumin <3 gm/dl (OR = 8.0) were risk factors associated with mortality and can guide in risk stratification. Hypoalbuminemia is a novel mortality risk factor, detected in this study, and requires further investigation to validate its utility as a prognostic marker and reveal possible therapeutic benefits in clinical correction.